Disulfiram-induced epileptic seizures - Nogueira, Violeta (BMJ Case Rep, 2021)
Disulfiram has been widely used for over six decades in the treatment of alcohol dependence, as an aversive therapeutic agent. Despite having very few side effects when taken without concurrent alcohol consumption, some of these may underlie serious clinical complications. Epileptic seizure induction is a rare adverse effect of disulfiram and its aetiological mechanism is unknown. We present a hospitalised 47-year-old male patient with two episodes of generalised tonic-clonic seizures during treatment with disulfiram while abstinent from alcohol.